Forward Contracts, Market Structure, and the Welfare Effects of Mergers - Nathan Miller; Joseph Podwol (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2017)
We examine how forward contracts affect economic outcomes under generalized market structures. In the model, forward contracts discipline the exercise of market power by making profit less sensitive to changes in output. This impact is greatest in markets with intermediate levels of concentration. Mergers reduce the use of forward contracts in equilibrium and, in markets that are sufficiently concentrated, this ampli-fies the adverse effects on consumer surplus. Additional analyses of merger profitability and collusion are provided. Throughout, we illustrate and extend the theoretical re-sults using Monte Carlo simulations. The results have practical relevance for antitrust enforcement.
Keywords: 330